Prospects and Challenges to Arms Control in South Asia - Qaisar, Muhammad Naveed (Journal of Arts & Social Sciences, 2020)
In recent past, India attempts to modernize its arm forces. The technological advancement in conventional precision strike together with perception of increasing advantage of offensive weapons has led to precarious Indo-Pakistan stability. As a consequence, the latter has reciprocated by increasing existing number of nuclear weapons and delivery means. The above mentioned technological and political developments have increasingly become risky with incentives to launch a first strike. As a result, security dilemma is increasing which may led to war. For ensuring deterrence stability it is imperative that both sides place certain limits on the offensive nature of their weapons system.Key words: India and Pakistan, Security dilemma, Anti-ballistic missile defense, tactical nuclear weapons,offense and defense, arms control